Development of a Virtual Laboratory with a Project for Teaching Complexometric Titration to Improve Learning Outcomes - Khoirul Bariah; Manihar Situmorang (Jurnal Akademika Kimia, 2026)
The teaching of complexometric titration has not yet utilized learning media that can foster student activity, so that, in terms of cognition, students' abilities remain low. Another problem was that experiments in complexometric titration were not conducted due to limited practical work time following the implementation of block learning. The purpose of this study is to develop a virtual laboratory project to teach complexometric titration and improve student learning outcomes. This research is a Research and Development study using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This study involved 72 students from two classes of the Chemistry Education study program in the 2023-2024 academic year. The research instruments used were a virtual laboratory feasibility questionnaire, a test, and a response questionnaire. The results showed that the virtual laboratory media had a feasibility of 87.22%, indicating it is highly feasible for use. Student learning outcomes from objective tests showed that the N-Gain in the class was 0.68, a significant increase compared to the control class's 0.55. The student response to the development of the virtual laboratory project is 87.65%, which falls in the very good category. Therefore, it can be concluded that developing a virtual laboratory with projects is highly feasible for use in complexometric titration instruction to improve student learning outcomes.